2024
DOI: 10.3390/agronomy14030625
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Incorporating Caraway into a Multi-Cropping Farming System on the Crops and the Overall Agroecosystem

Aušra Rudinskienė,
Aušra Marcinkevičienė,
Rimantas Velička
et al.

Abstract: The scientific aim of this article is to investigate the potential benefits of implementing a multi-cropping system, specifically focusing on the incorporation of caraway, to improve soil agrochemical and biological properties, prevent soil degradation and erosion, and ultimately enhance soil quality and health to better adapt to climate change. This study aims to provide valuable insights into the comparative analysis of various soil parameters and biological indicators to showcase the promising perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…In our study, although intercropping does enhance the soil urease, invertase, catalase and acid phosphatase activities under the same straw treatment, this effect (magnitude of increase) is evidently weaker in the rhizosphere of soybean than that of maize. Rudinskiene et al reported that intercropping increases crop yields and soil nutrient availability, but the soil enzymes’ activity differs little from that of monocultures [ 53 ]. According to other research, straw incorporation bolsters the activities of key soil enzymes [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although intercropping does enhance the soil urease, invertase, catalase and acid phosphatase activities under the same straw treatment, this effect (magnitude of increase) is evidently weaker in the rhizosphere of soybean than that of maize. Rudinskiene et al reported that intercropping increases crop yields and soil nutrient availability, but the soil enzymes’ activity differs little from that of monocultures [ 53 ]. According to other research, straw incorporation bolsters the activities of key soil enzymes [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%